Healthy older adults balance pattern under dual task conditions: exploring the strategy and trend - Bahareh Zeynalzadeh Ghoochani; Seyed Ali Hosseini; Saeed Talebian; Akbar Biglarian; Afsaneh Zeinalzadeh; Salman Nazary-Moghadam; Seyed Alireza Derakhshanrad (Tabriz University of Medical Sciences, 2016)
Background: In line with health promotion plans, early intervention and fall prevention in geriatric population, it is important to study healthy individuals balance mechanisms. The aim of this research was to investigate the effect of adding and removing visual input and dual task on elderly balance. Methods: Twenty healthy elderly recruited from four different senior citizen health club centers and from the University of Social Welfare and Rehabilitation Sciences (USWR) participated in this analytic cross-sectional study. At USWR's Motor Control Laboratory, the participants' postural sway were assessed using force plate in 4 distinct double leg standing conditions with and without presence of visual input and Stroop dual task. Postural and Stroop variables were compared. Results: Findings indicated that when the elderly encountered with either dual task or absence of visual input, they can still manage the situation in a way that changes in sway parameter would not become significant. But, when these two conditions occurred simultaneously, the participant's balance strategy fluctuated. Therefore, the mean velocity showed a significant difference between the "single quiet standing" condition and the condition of standing with eyes closed while the participants were answering Stroop dual task (Mean difference = -0.007, 95% CI = -0.012, -0.002). Conclusion: It appears that velocity parameter is sensitive to small changes, so it is recommended that researchers include this parameter in their future analyses. Balance in elderly can be manipulated by dual task and visual input deprivation.